Pregnancy Outcome Among Primigravidae Aged 35 Years and Above: A Comparative Study - Singh, Kritina; Shrestha, Prashant; Baaniya, Jeena; Gurung, Prashana (Journal of Lumbini Medical College, 2020)
Introduction: Maternal age is an important determinant of pregnancy outcome. Women aged 35 years or more at their first pregnancy are considered high risk as they are associated with increased adverse maternal and perinatal outcomes. Methods: A retrospective, comparative study was carried out over a period of two years in a tertiary center. Each elderly primigravida was matched with two primigravid women aged 20-34 years who delivered during the same period. Secondary data on obstetric outcomes (diabetes, oligohydramnios, polyhydramnios, hypothyroidism), postpartum complications (post-partum hemorrhage, postpartum eclampsia) and perinatal outcome (intra-uterine growth restriction, prematurity, congenital anomalies, and neonatal death)of 82 elderly primigravidae (study group) was compared to 164 younger primigravida (control group) delivered during the period of study. The Chi Square test and Fisher’s Exact test were used for statistical analysis and p value of <0.05 was taken as level of significance. Results: During the study period, there were 15,012 deliveries and 82 of these were elderly primigravidae giving an incidence of 0.55%. The mean age of the elderly primigravidae was 36.8±2.16 years. The study group had more antepartum complications with preterm labor, diabetes in pregnancy, hypertensive disorders in pregnancy, multiple pregnancy and polyhydramnios (p<0.05). Seventy-one elderly primigravidae were delivered by caesarean section, the commonest indication being maternal request. The study group had higher incidence of post-partum hemorrhage but no perinatal mortality of significant proportion. Conclusion: Maternal age at the first pregnancy influences pregnancy and neonatal outcomes. Hence, elderly primigravidae should be considered as high risk and followed up accordingly.